2021
DOI: 10.1109/access.2021.3070112
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Lead-Free Perovskite Solar Cell for 17.83% Efficiency

Abstract: Distributed Source Coding (DSC) schemes rely on separate encoding but joint decoding of statistically dependent sources, which exhibit correlation. More specifically, Distributed Joint Source-Channel coding (DJSC) is associated with the scenario, where the correlated source signals are transmitted through a noisy channel. On one hand, employing DSC or DJSC schemes exploits the existing correlation between sensors resulting in minimising the transmission energy required by the sources, while maintaining reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Therefore, for the highly efficient photovoltaic response, the physical parameters such as electron affinity, energy bandgap, doping density, and film thickness of ideal hole and electron transport layers were determined for the Cs 2 TiBr 6 -based solar cell through SCAPS-1D simulation. It was observed that the proper hole transport layer (electron affinity = −3 eV, energy band gap = 3 eV, N a =10 20 cm −3 , and thickness = 250 nm), as well as using the appropriate electron transport layer (electron affinity = −4.6 eV, energy band gap = 4 eV, N d =10 16 cm −3 , and thickness = 25 nm), can give a maximum PCE up to 20.41% for Cs 2 TiBr 6 -based perovskite solar cells. Unfortunately, not a single hole and electron transport material with the required electronic structure was found.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, for the highly efficient photovoltaic response, the physical parameters such as electron affinity, energy bandgap, doping density, and film thickness of ideal hole and electron transport layers were determined for the Cs 2 TiBr 6 -based solar cell through SCAPS-1D simulation. It was observed that the proper hole transport layer (electron affinity = −3 eV, energy band gap = 3 eV, N a =10 20 cm −3 , and thickness = 250 nm), as well as using the appropriate electron transport layer (electron affinity = −4.6 eV, energy band gap = 4 eV, N d =10 16 cm −3 , and thickness = 25 nm), can give a maximum PCE up to 20.41% for Cs 2 TiBr 6 -based perovskite solar cells. Unfortunately, not a single hole and electron transport material with the required electronic structure was found.…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, SCAPS 1D (version 3.3.07) simulation software was used to determine the most suitable hole and electron transport parameters for the highly efficient Cs 2 TiBr 6 -based perovskite solar cell [16,26]. The SCAPS-1D is a one-dimensional simulation software that uses the combination of well-defined mathematical equations such as the Poisson equation (Equation ( 1)), electron continuity equation (Equation ( 2)), hole continuity equation (Equation (3)), total charge transport equation (Equation ( 4)), total charge transport equation for the electron (Equation ( 5)), total charge transport equation for the hole (Equation ( 6)), and optical absorption coefficient equation (Equation ( 7)) to define the photovoltaic response of a solar cell.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 3 more Smart Citations